2007
DOI: 10.1080/10425170701308956
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the Senegal sole,Solea senegalensisKaup. Comparative analysis of tandem repeats in the control region among soles

Abstract: The complete nucleotide sequence of the mitochondrial genome for the Senegal sole Solea senegalensis Kaup was determined. The mitochondrial DNA was 16,659 base pairs (bp) in length. Sequence features of the 13 protein-coding genes, two ribosomal RNAs and 22 transfer RNAs are described. The non-coding control region (1017 bp) was compared with those of the closely related soles Solea solea and Solea lascaris. The typical conservative blocks were identified. A cluster of 42 and 22 tandemly arrayed repeats was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Furthermore, a typical gene order and large-scale gene rearrangements have been found within the teleost genus Symphurus (Shi et al, 2015a). In contrast, no gene rearrangements have been identified in soles (Soleidae), even though they are the closest family to the Cynoglossidae (Shi et al, 2014b;Manchado et al, 2007;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, a typical gene order and large-scale gene rearrangements have been found within the teleost genus Symphurus (Shi et al, 2015a). In contrast, no gene rearrangements have been identified in soles (Soleidae), even though they are the closest family to the Cynoglossidae (Shi et al, 2014b;Manchado et al, 2007;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 89%
“…Additionally, it contains two functional non-coding regions: the lightstrand (L-strand) replication origin (O L ) and the control region (CR). Gene order in vertebrate mtDNA is thought to be quite conserved, especially in fishes (Clayton, 1992;Manchado et al, 2007). However, an increasing number of gene rearrangements in mtDNA have been identified in many taxa, including reptiles (Mueller and Boore, 2005;Okajima and Kumazawa, 2010), birds (Bensch and Harlid, 2000;Schirtzinger et al, 2012;Verkuil et al, 2010), amphibians (Macey et al, 1997;Sano et al, 2005), and fishes (Gong et al, 2013a;Inoue et al, 2003;Kong et al, 2009;Ki et al, 2008;Mabuchi et al, 2004;Ponce et al, 2008;Shi et al, 2013Shi et al, , 2014aShi et al, , 2015a.…”
Section: Introductionmentioning
confidence: 97%
“…The AT contents of the CRs reach up to 64.4% to 66.7%, which are higher than those of the whole mtDNA sequences. The symbolic structures of the CRs are observed as in other fishes (Figure 3), including the extended termination associated sequence (ETAS, containing TAS-cTAS: TACAT-ATGTA), central conserved sequence blocks (CSB-F,E,D), G-BOX (GTGGGGG), pyrimidine tract (poly-T), and conserved sequence blocks (CSB 2-3) (Nesbo et al 1998;Manchado et al 2007;Wang et al 2013). …”
Section: Non-coding Sequencesmentioning
confidence: 87%
“…So far, the sequences of some conserved blocks have not been defined. Generally, only the TAS, CSB-F, E, and D of the central conserved blocks are identified in most fishes, while the CSB-C, B, and A are greatly variable (Lee et al 1995;Guo et al 2003;Manchado et al 2007;Zhang et al 2010), and CSB-1,2,3 have been found only in some fishes (Lee et al 2001;Liu 2002;Guo et al 2003).…”
Section: Non-coding Sequencesmentioning
confidence: 99%
“…Furthermore, some structural features, such as gene rearrangements, could exist in some fish, which are typically explained by the recombination model, tandem duplication and random loss model (Dowton et al, 2003). Although more than one thousand complete mtDNA sequences have been reported in teleostean fish (http://www.ncbi.nlm.nih.gov/ genomes/ORGANELLES/taxtree.cgi?db=Mito&taxid=2759&result= frame&complete=All&initrankid=1) and the organization in most fish mtDNA genomes is quite conserved (Manchado et al, 2007), only a few reports have appeared on gene rearrangements in fish mt genomes, such as flatfishes (Inoue et al, 2004;Papetti et al, 2007;Ki et al, 2008;Kong et al, 2009;Shi et al, 2014;Fonseca et al, 2014). These studies revealed that the gene rearrangements and their variations could be very useful to better understand the molecular genetics and evolution of mt genomes and to infer evolutionary relationships (SanMauro et al, 2006;Amer and Kumazawa, 2007).…”
Section: Introductionmentioning
confidence: 99%